STUDY OF 3D PRINTING HIPS BREAST PHANTOM MATERIAL: EFFECT OF EXPOSURE VOLTAGE VARIATION AND NODULE SIZE - Yunianto, Mohtar; Devi, Nanda Astika; Anwar, Fuad; Cindyana, Adnan (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
A study has examined the characteristics of 3D printer materials of HIPS and PLA. The study began by printing HIPS materials that resembled breast organs and PLA materials that resembled breast cancer nodules. Then it exposed them using a CT scan with voltage variations of 80 kV, 100 kV, and 120 kV. The parameters studied were compared with the reference breast organ. The results obtained at these voltages obtained CT-number values sequentially (-85.14+0.25) ; (-64.79+0.21) HU; (-55.08+0.18) HU values from the reference 35 to -94 HU, relative electron density values sequentially 0.915; 0.935; 0.945 with a reference value of 0.950, the density value of the material obtained is (0.921+0.002) g/, The EDG value is 3.24 x  from ICRU 1989 was 3.33 x, The EDV value is (3.00 + 0.01) x  from ICRU report 44 was 3.18 x 10, the value is 3.50 the value of ICRU data is 3.28, and the effective dose values are respectively 2.53 mSv, 2.83 mSv, 3.20 mSv. Based on these characteristics, the results indicate that the breast phantom matches the characteristics of the breast organ, allowing it to be used to predict the presence of breast cancer, as it shares the same characteristics. The results of exposure to the lung cancer nodule phantom on the CT-Scan image of the 2 mm nodule size are not visible. The results of this study can be used as a consideration for radiologists when choosing a voltage based on the predicted size of the breast cancer nodule.